2020
DOI: 10.1007/s43032-020-00396-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temperature and Time Interval Prior to Immature Testicular-Tissue Organotypic Culture on Cellular Niche

Abstract: Cryopreservation of immature-testicular-tissue (ITT) prior to gonadotoxic treatment, while experimental, is the only recommended option for fertility preservation in prepubertal boys. The handling and manipulation of ITT before cryopreservation could influence the functionality of cells during fertility restoration, which this study explored by evaluating cellular niche and quality of mouse ITT subjected to various temperatures and time durations in vitro. ITT from 6-day-old mice were handled at ultraprofound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The holding phase interval was scheduled as 6 and 24 h, corresponding to short-range and long-range shipment. Post holding, these testes were processed for organotypic culture as described previously ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The holding phase interval was scheduled as 6 and 24 h, corresponding to short-range and long-range shipment. Post holding, these testes were processed for organotypic culture as described previously ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, studies have determined the optimal conditions for ITT such as tissue size, storage temperatures, and storage periods in various models including human tissue ( 7 11 ). Recently, our group has demonstrated that ITT manipulation at 4°C had a minimal negative impact on the organotypically cultured germ cell population when compared to room temperature and 37°C ( 12 ). However, we believe that it is important to address the epigenetic integrity of germ cells from cultured ITT as epigenetic aberrations may negatively affect the subsequent developmental process.…”
Section: Introductionmentioning
confidence: 99%
“…The other fragments were cultured in a modified testicular explant culture system established by Sato et al (2011) at 35 • C and 5% CO 2 [24,28,32]. For the gel stands, 0.07 g agarose (#A9639, Sigma-Aldrich, St. Louis, MO, USA) was heated in 10 mL cell culture grade deionized water using a water bath.…”
Section: Organ Culturementioning
confidence: 99%